Public Sentiment Analysis of the Free Nutritious Meals Program (MBG) on Social Media X Using the Naive Bayes Method - Aprianti, Ni Nyoman; Desmayani, Ni Made Mila Rosa; Libraeni, Luh Gede Bevi; Indrawan, I Gusti Agung; Radhitya, Made Leo (Journal of Applied Informatics and Computing, 2025)
This study aims to analyze public sentiment towards the Free Nutritious Meals Program (MBG) launched by the government, utilizing data from the X (Twitter) platform using the Naïve Bayes method. The background of this study is based on the high level of public attention towards the MBG program, which targets school children, toddlers, pregnant women, and nursing mothers, as well as the prevalence of diverse opinions on social media. Data was collected through a crawling process during the period of April 28 to May 28, 2025, using keywords related to MBG, resulting in 12,310 tweets. The data processing stages included text preprocessing (cleansing, case folding, tokenizing, filtering, stemming), word weighting with TF-IDF, training and test data division, and testing using a confusion matrix. The results show that the Naïve Bayes method is capable of classifying sentiment into three categories: positive, negative, and neutral, with optimal performance on an 80:20 data split, resulting in an accuracy of 86.78%, precision of 86.86%, recall of 86.78%, and an F1-score of 86.58%. The majority of public sentiment towards the MBG program was positive, reflecting support for the program's benefits in improving the nutrition of school children and alleviating the economic burden on families. This study is expected to serve as a reference for the government in evaluating public policy and communication strategies, as well as contributing academically to the development of text mining and sentiment analysis studies on social media.